2017
DOI: 10.7554/elife.28672
|View full text |Cite
|
Sign up to set email alerts
|

HMMR acts in the PLK1-dependent spindle positioning pathway and supports neural development

Abstract: Oriented cell division is one mechanism progenitor cells use during development and to maintain tissue homeostasis. Common to most cell types is the asymmetric establishment and regulation of cortical NuMA-dynein complexes that position the mitotic spindle. Here, we discover that HMMR acts at centrosomes in a PLK1-dependent pathway that locates active Ran and modulates the cortical localization of NuMA-dynein complexes to correct mispositioned spindles. This pathway was discovered through the creation and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 64 publications
3
58
0
1
Order By: Relevance
“…The synergistic regulation of FAM83D and HMMR, along with their constitutive interaction, suggested a possible role for HMMR in the regulation of FAM83D and CK1a in mitosis ( Fig 4G). Indeed, as observed in U2OS cells, a robust mitotic phospho-FAM83D mobility shift was evident in wild-type MEFs, but this shift was completely absent in the HMMR knockout MEFs [15] ( Fig 4H). This is consistent with the notion that HMMR directs FAM83D to the spindle [16], and hence, in the absence of HMMR, FAM83D no longer localises to the mitotic spindle and is not phosphorylated.…”
Section: Of 19supporting
confidence: 61%
See 2 more Smart Citations
“…The synergistic regulation of FAM83D and HMMR, along with their constitutive interaction, suggested a possible role for HMMR in the regulation of FAM83D and CK1a in mitosis ( Fig 4G). Indeed, as observed in U2OS cells, a robust mitotic phospho-FAM83D mobility shift was evident in wild-type MEFs, but this shift was completely absent in the HMMR knockout MEFs [15] ( Fig 4H). This is consistent with the notion that HMMR directs FAM83D to the spindle [16], and hence, in the absence of HMMR, FAM83D no longer localises to the mitotic spindle and is not phosphorylated.…”
Section: Of 19supporting
confidence: 61%
“…Beyond CK1a, the phosphorylation-mediated control of spindle positioning has been attributed to several other protein kinases. Of note, the activity of CDKs, PLKs and Aurora kinases have all been shown to critically regulate spindle positioning [15,[43][44][45][46][47][48][49][50]. Both their recruitment to the mitotic spindle and activities are tightly regulated [44,46,51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we sought to investigate the FAM83D protein, and define its physiological role in relation to CK1 isoforms. Although FAM83D (aka CHICA) is poorly characterised, it has been shown to be recruited to the mitotic spindle through its association with the microtubule-associated protein hyaluronan mediated motility receptor (HMMR, aka RHAMM or CD168) (Connell, Chen et al, 2017, Dunsch, Hammond et al, 2012, Santamaria, Nagel et al, 2008. Unlike the other FAM83 members that appear to associate robustly with CK1a, we found that over-expressed GFP-FAM83D in asynchronous cell extracts interacted rather weakly, yet selectively, with CK1α (Fulcher et al, 2018), suggesting this could be a regulated interaction.…”
mentioning
confidence: 74%
“…Consistent with this, in the course of an unbiased proteomic approach to identify interactors of endogenous FAM83D from both asynchronous and mitotic extracts, we discovered in this study that FAM83D interacts with CK1a only in mitosis. As the kinetics of chromosomal alignment are delayed and the cell division axis is altered following the depletion of FAM83D by siRNA, as well as in cells lacking HMMR or those derived from HMMR knockout mice (Connell et al, 2017, Dunsch et al, 2012, Santamaria et al, 2008, we hypothesised that these phenotypes could be potentially explained by the non-delivery of CK1α to the spindle in the absence of FAM83D or HMMR. Here, we show that the FAM83D-CK1α interaction is critically important for correct and efficient spindle positioning, as well as smooth progression through the cell division cycle.…”
mentioning
confidence: 99%